Analisis Konseptual Implementasi Akuntansi Syariah terhadap Keberlanjutan, Etika, dan Kepercayaan dalam Pelaporan Keuangan - Andinah Alfia Azzahra; Andi Devtriana Alya Nabila; Masyhuri Masyhuri (Journal of Economic and Business Advancement, 2025)
This study presents a conceptual analysis of the implementation of Sharia accounting and its contributions to sustainability, ethics, and trust in financial reporting. The significant growth of the Islamic finance industry in Indonesia, with total Sharia banking assets reaching IDR 892 trillion in 2023, underscores the urgency of adopting transparent reporting systems grounded in Islamic value principles. The study integrates literature on fundamental Sharia accounting principles, social responsibility, and ethical governance to examine the relationship between Sharia-compliant reporting and the enhancement of stakeholder trust. A qualitative descriptive approach through literature review is employed to map how principles of justice, integrity (amanah), and accountability strengthen the reliability of financial statements while promoting the sustainability of Sharia financial institutions. The findings indicate that Sharia accounting has the potential to serve as a reporting framework that not only meets professional standards but also internalizes moral and spiritual values, thereby reinforcing public trust and supporting a sustainable Islamic financial ecosystem.